Efektivitas Manajemen Supervisi Akademik dalam Mendukung Implementasi Kurikulum Merdeka di SDN 44 Rejang Lebong - Winda Sari Dewi; Abdul Rahman (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
Educational transformation through the implementation of the Merdeka Curriculum demands not only teacher readiness but also effective academic supervision. Academic supervision plays a vital role in ensuring that teachers are capable of implementing differentiated instruction, formative assessment, and student-centered learning strategies. This study aims to analyze the effectiveness of academic supervision in supporting the implementation of the Merdeka Curriculum at SD Negeri 44 Rejang Lebong and to identify the challenges and supports involved in its implementation. The research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and document analysis. Informants were selected purposively, consisting of the principal, supervisor, and teachers involved in the curriculum implementation. Data analysis was conducted using thematic analysis with triangulation of sources, methods, and theories. The findings reveal that academic supervision is still largely administrative and lacks focus on pedagogical aspects. Identified barriers include insufficient training for supervisors, limited teacher understanding of differentiated learning, and minimal follow-up after supervision. However, reflective, continuous, and needs-based supervision has proven to enhance teacher competence and the effectiveness of the Merdeka Curriculum implementation. The limitation of this study lies in its scope, which is confined to a single school, yet it provides significant implications for developing contextual academic supervision practices. This research offers an original contribution by proposing a reflective supervision approach that aligns with teachers’ needs and the challenges of implementing a new curriculum in elementary schools